2016
DOI: 10.1007/s00464-016-4994-7
|View full text |Cite
|
Sign up to set email alerts
|

Validation of difficulty scoring system for laparoscopic liver resection in patients who underwent laparoscopic left lateral sectionectomy

Abstract: The surgical difficulty varies among patients undergoing the same laparoscopic LLS procedure. The modified DSS developed here can also be applied to patients with IHD stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…12 To date, only a few authors have used the DSS for comparative analysis of LLR results. 22 In our series, anatomic parenchymasparing resection of posterosuperior segments with vascular involvement proved to be the most complex procedure, according to the DSS.…”
Section: Discussionmentioning
confidence: 81%
“…12 To date, only a few authors have used the DSS for comparative analysis of LLR results. 22 In our series, anatomic parenchymasparing resection of posterosuperior segments with vascular involvement proved to be the most complex procedure, according to the DSS.…”
Section: Discussionmentioning
confidence: 81%
“…Ban et al . 11 proposed the Iwate difficulty scoring system to assess the difficulty of LLR in 2014, and subsequent studies have validated this scoring system and confirmed its usefulness 1215 . When the Iwate difficulty scoring system is used to classify patients into low-, intermediate-, and high-risk groups, the intraoperative blood loss volume and operation time reportedly significantly differ between the low- and high-risk groups and between the intermediate- and high-risk groups, but not between the low- and intermediate-risk groups 11 .…”
Section: Discussionmentioning
confidence: 97%
“…Ban et al . 11 introduced a difficulty scoring system to assess the difficulty of LLR, and some studies have validated this scoring system 1215 . However, it is difficult to use the scoring system to evaluate the difficulty of LRH, as the system does not assess factors related to repeat hepatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Factors affecting the difficulty include tumor location, tumor size, presence of cirrhosis, and proximity to major vessels. This grading system has been validated by several centers [97][98][99]. It is generally agreed that the system provides a good reflection of the complexity of the surgery.…”
Section: Hcc With Portal Vein Invasionmentioning
confidence: 99%